Comparing the impact of management support on police officers' perceptions of discretionary power and engagement: Australia, USA and Malta. Issue 6 (25th March 2020) - Brunetto, Yvonne; Farr-Wharton, Ben; Farr-Wharton, Rod; Shacklock, Kate; Azzopardi, Joseph; Saccon, Chiara; Shriberg, Art
Abstract: This paper uses Social Exchange Theory as a lens for comparing the impact of management support upon police perceptions of discretionary power and employee engagement, across three countries. A survey-based, self-report process collected data from 193 police officers in Australia, 588 from the USA, and 249 from Malta. Structural equation modelling was used to analyse the data. The findings suggest a significantly different management support context across the three countries, as well as significantly different perceptions of discretionary power. Across the three countries, police perceived relatively poor satisfaction with organizational management support and only some engagement levels. However, USA police perceived significantly more discretionary power than the other country samples. These findings provide greater clarity about the link between management support, discretionary power and engagement for the police officers. Since employee engagement likely affects policing outcomes, the findings suggest that poor management support of police officers could negatively affect the provided service. Potential strategies to enhance police engagement include (a) training police managers about how to manage so as to promote greater engagement, and (b) modifying police managers' performance indicators in line with achieving better police engagement.